Post‐fire vegetation response at the woodland–shrubland interface is mediated by the pre‐fire community. Issue 6 (12th June 2017) - Urza, Alexandra K.; Weisberg, Peter J.; Chambers, Jeanne C.; Dhaemers, Jessica M.; Board, David
Abstract: Understanding the drivers of ecosystem responses to disturbance is essential for management aimed at maintaining or restoring ecosystem processes and services, especially where invasive species respond strongly to disturbance. In this study, we used repeat vegetation surveys from a network of prescribed fire treatments at the woodland–shrubland interface in the Shoshone Mountains, Nevada, USA, to investigate post‐fire responses of the understory plant community. First, we characterized post‐fire community trajectories for sites located along an elevational gradient, hypothesizing a positive relationship between elevation and resistance to invasion. Unburned understory communities and their responses to disturbance differed along the gradient. As hypothesized, lower elevations experienced greater species turnover and higher invasive annual grass ( Bromus tectorum ) cover after fire. Second, we characterized post‐fire plant community trajectories for sites with varying levels of pre‐fire pinyon and juniper cover, hypothesizing that pre‐fire tree dominance and associated reductions in perennial understory species lead to less predictable post‐fire trajectories. Among sites with low‐to‐moderate tree cover, burning largely eliminated differences in understory composition, suggesting that biotic legacies were sufficient to result in predictable trajectories. In contrast, sites with high pre‐fire tree cover transitioned into an annual forb‐dominated community with sparse vegetation cover, suggesting that the loss of the understory community initiated unpredictable and divergent post‐fire trajectories. Because plant communities were still changing four years after fire, it is unclear whether the alternate trajectories in sites with high tree cover will result in the formation of alternate states, or whether community composition will eventually converge with other sites at the same elevation. Results indicate that careful evaluation of site characteristics can be used to predict treatment outcomes at the woodland–shrubland interface, and to guide the appropriate use of prescribed fire or other management practices.